Deep inelastic scattering at HERA - Foster, B (1998)
Results from the HI and ZEUS experiments at HERA on deep inelastic scattering are reviewed. The data lead to a consistent picture of a steep rise in the F2 structure function and in the gluon density within the proton. Important new information on the partonic structure of diffraction is emerging from H1 and ZEUS. The spacelike region in which the weak and electromagnetic interactions become of equal strength is being explored for the first time. A possible excess of events at high x and Q2 compared to the expectations of the Standard Model has been observed in both experiments. © World Scientific Publishing Company.